![image](https://tex.z-dn.net/?f=%28x-2%29%5E2%5Cgeq3%3B%5C%5C+%5Cleft+%5B+%7B%7Bx-2%5Cgeq%5Csqrt3%7D+%5Catop+%7Bx-2%5Cleq-%5Csqrt3%7D%7D+%5Cright.%5C+%5C+%5Cleft+%5B+%7B%7Bx%5Cgeq2%2B%5Csqrt3%7D+%5Catop+%7Bx%5Cleq2-%5Csqrt3%7D%7D+%5Cright.%3A%3D%3D%3E%5C%5C+%3D%3D%3E%5C+x%5Cin%5Cleft%28-%5Cinfty%3B2-%5Csqrt3%5Cright%5D%5Ccup%5Cleft%5B2%2B%5Csqrt3%3B%2B%5Cinfty%5Cright%29%3B)
\\ ==>\ x\in\left(-\infty;2-\sqrt3\right]\cup\left[2+\sqrt3;+\infty\right);" alt="(x-2)^2\geq3;\\ \left [ {{x-2\geq\sqrt3} \atop {x-2\leq-\sqrt3}} \right.\ \ \left [ {{x\geq2+\sqrt3} \atop {x\leq2-\sqrt3}} \right.:==>\\ ==>\ x\in\left(-\infty;2-\sqrt3\right]\cup\left[2+\sqrt3;+\infty\right);" align="absmiddle" class="latex-formula">
Имеем ответ:
![image](https://tex.z-dn.net/?f=%5Csqrt%7B%28x-2%29%7D%5Cgeq3%3B%5C%5C%0AD%28f%29%3A+x-2%5Cgeq0%3D%3D%3Ex%5Cgeq2%3B%3D%3D%3Ex%5Cin%5B2%3B%2B%5Cinfty%29%3B%5C%5C%0Ax-2%5Cgeq9%3B%5C%5C%0Ax%5Cgeq11%5C%5C%0Ax%5Cin%5B11%3B%2B%5Cinfty%29%3B)
x\geq2;==>x\in[2;+\infty);\\
x-2\geq9;\\
x\geq11\\
x\in[11;+\infty);" alt="\sqrt{(x-2)}\geq3;\\
D(f): x-2\geq0==>x\geq2;==>x\in[2;+\infty);\\
x-2\geq9;\\
x\geq11\\
x\in[11;+\infty);" align="absmiddle" class="latex-formula">